Tinjauan Kuat Tekan dan Kuat Tarik Kayu Berdasarkan PKKI 1961, SNI M. 27 – 1991 – 03 dan SNI M. 25 – 1991 – 03 - Kistiani, Frida (Department of Civil Engineering, Diponegoro University, 2006)
Wood is as one of building materials which has a specific characteristic compared to others such as steel and concrete. As a natural material wood has natural mechanical characteristics. Wood classifies as anisotrophic material which has different mechanical characteristic within its stress, tension, bending, and shear. (it has stresses in inline, perpendicular, and in skewed angle with fibre direction). The various of it skewness of wood’s fibre, humidity, age, and specific gravity has significant influence to the mechanical characteristic of the wood. The purpose of this paper is to explain how the differences of mechanical characteristic. Therefore a certain wood probably has many types of various fibre directions. This paper focuses to study on wood stress and tension characteristics.Keywords: specific characteristik of wood, anisotrophic, influence factors, tension and stressPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3947[How to cite: Kistiani, F., 2006, Tinjauan Kuat Tekan dan Kuat Tarik Kayu Berdasarkan PKKI 1961, SNI M. 27 – 1991 – 03 dan SNI M. 25 – 1991 – 03, Jurnal Media Komunikasi Teknik Sipil, Volume 14, Nomor 2, pp. 206-212]